Desain Oil Spill Recovery Boat Untuk Area Pelabuhan Tanjung Priok - Andreo Marthen; Arif Fadillah; Putra Pratama (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
In recent years, trade traffic through Tanjung Priok Port has always increased. An increase in the economy always has a negative impact on the environment. Because every ship that docks has the potential to dump waste in the port area. Most of the causes of marine pollution in Indonesia are caused by ship waste, of course this is related to the lack of awareness of ship operators about the cleanliness of the environment around the port. Related to this, this research was conducted to plan an environmentally friendly Oil Spill Recovery Boat, by using electric power for navigation and communication needs. Oil spill control vessel design. This Oil Spill Recovery Boat has a catamaran hull designed using the Maxsurf application. The method used to determine the main size of the Oil Spill Recovery Boat is linear regression, namely by using comparison vessels that have been compiled and then adjusted to the number of oil spills in the research area. By using Maxsurf software, the main dimensions obtained are L = 10.0 m, B = 4.42 m, H = 1.34 m and T = 0.61 m.. This ship has a crew of 3 people.